A cry in unison : sistering for survival - Cohen, Judy Weissenberg 1928- (The Azrieli series of Holocaust survivor memoirs ,, 2020)
"The memoir of Judy Weissenberg Cohen, who grew up in Debrecen, Hungary, before World War II, and then survived the Holocaust and came to Canada after the war. When the Nazis invade Hungary in 1944, Judy and her family are placed in a ghetto and then deported to Auschwtiz-Birkenau. There she survives with the support of her sisters and other women in the camps. She is then sent to Bergen-Belsen and then Ascherlseben, a sub camp of Buchenwald, where she does forced labour in a Junkers airplane parts factory. Judy survives a death march and is liberated by the US Army. After the war, she reunites with two of her siblings in the Bergen-Belsen DP camp, after which she makes her way to Montreal as a seamstress with the Tailor Project. Judy marries, moves to Toronto and raises a family and then becomes involved in Holocaust education, specifically in the realm of gender studies and the Holocaust, launching a website about women's experiences in the Holocaust."--